Kegiatan Sosialisasi Telkom Solution Business Partner (TSBP) Dalam Meningkatkan Sikap Karyawan Menangani Kasus Pelanggan Telkom Solution - Dian Dwiyane (KOM & REALITAS SOSIAL, 2011)
PT. Telekomunikasi Indonesia Tbk. is the largest company engaged in communications services, to full fill the needs of telecommunications in a growing business world. PT. Telekomunikasi Indonesia Tbk. (Telkom) launched "TELKOM Solution", an InfoCom service which is integrated with the main target corporate market (high-end market). "TELKOM Solution" concerned the quality aspects and highlight the benefits also value to the business world. This research, examine socialization activities taken by the management of PT. Telekomunikasi Indonesia Tbk. about "TELKOM Solution". The socialization gives information about the services offered by "TELKOM Solution". The socialization of "TELKOM Solution" is being concept in a message or subject matter given by PT Telekomunikasi Indonesia, tbk. PT Telekomunikasi Indonesia, tbk. gives message about the system of "TELKOM Solution" service , the goal is to avoid the acknowledge about the excellence and function of "TELKOM Solution" service.